Molecular identification and phylogenetic relationships of seven Satyrinae butterflies in Bangladesh using Cytochrome c oxidase subunit I gene (Jahangirnagar University Journal of Biological Sciences, 2019)
The Satyrinae is a subfamily of Nymphalid butterfly, which is morphologically and ecologically the most diverse group, occurring in all habitats. In the present study, Cytochrome c oxidase subunit I (COI) gene of seven species of Satyrinae was sequenced, aligned, and used to construct phylogenetic trees. The molecular identification of these Satyrinae species was confirmed by comparing the related sequences in the National Center for Biotechnology Information (NCBI) GenBank. The base compositions of the COI sequences were 39.07% T, 16.44% C, 29.83% A, and 14.64% G, revealing a strong AT bias (68.9%). The sequence distance among Satyrinae species ranged from 0.09% to 0.18%. Phylogenetic trees were constructed by the neighbor-joining (NJ) and maximum likelihood (ML) methods, using Orthetrum sabina as an outgroup. Both trees had almost identical topologies. The sampled species in Satyrinae exhibited the following relationships: Melanitis leda + [(Mycalesis mineus+(Mycalesis gotama+Mycalesis anaxias)) + (Ypthima baldus + (Lethe chandica+Elymnias hypermnestra))], suggesting that M. leda might be distantly related with the rest of the Satyrinae species. This clustering result is almost identical to current traditional classification. This study confirms that the COI based DNA barcoding is an efficient method for the identification of butterflies including Satyrinae species and, as such, may further contribute effectively to biodiversity and evolutionary research.Jahangirnagar University J. Biol. Sci. 8(1): 67-74, 2019 (June)